An investigation of a Kerlan-Jobe Orthopaedic Clinic shoulder and elbow score in elite canoe slalom: Establishing measurement properties to make practice recommendations. (July 2021) - Powell, Andrew; Williamson, Samuel; McCaig, Steven; Heneghan, Nicola R.; Horsley, Ian
Abstract: Objective: To investigate the test-retest reliability and validity of the Kerlan-Jobe Orthopaedic Clinic shoulder and elbow score (KJOC) in elite Canoe Slalom athletes and determine its ability to predict future shoulder pain. Design: Observational study with embedded test-retest reliability study. Setting: British Canoe Slalom National Training Centre. Participants: Nineteen athletes from the British Canoe Slalom team for the 2019 season. Main outcome measures: The KJOC was completed at the start of winter training and start of the 2019 competitive season. Current, historical (6-months pre-questionnaire) and prospective (4-months post-questionnaire) shoulder injuries were recorded. Results: Test-retest reliability was found to be excellent (ICC3, 1  = 0.97), with a minimal detectable change (MDC95% ) of 6.7. Compared to uninjured athletes, currently injured and historically injured athletes scored significantly lower (p = 0.002 and p = 0.011, respectively), with the difference between means > MDC95% . A cut-off of 88 was found to be predictive of shoulder pain (AUC: 0.779; sensitivity: 0.60; specificity: 0.95; positive likelihood ratio: 11.4). Conclusion: The KJOC demonstrated excellent reliability and can distinguish between athletes with and without current or historical shoulder pain. A KJOC score of <88 was associated with increased risk of shoulder pain. The KJOC should be completed as part of a risk profile for shoulder pain. Highlights: The KJOC is able to distinguish between athletes with and without a shoulder injury. The KJOC has good-excellent reliability. The KJOC MDC95% is 6.7. A KJOC of <88 is associated with shoulder pain/injury in the following 4-months.